More Harm than Good? A Pilot of a Motivational Interviewing Based Intervention for Increasing Readiness to Improve Nutrition in Young People Experiencing a First Episode of Psychosis. (2nd January 2019) - Fulton, Emily; Peet, Malcolm; Williamson, Kevin
The relationship between nutrition and mental health, as well as physical health, is well known. Mental Health Services in the UK and worldwide are recognising the need for nutritional care, however eliciting a change in eating habits in patients/service users is a challenge. The effects of a 'Psych-Nutritional Intervention' (PNI) using Motivational Interviewing (n = 30) was compared with a 'Treatment as Usual' (TAU) involving standard nutritional advice (n = 21) and a control group (no nutritional support) (n = 22). The sample consisted of young people aged 18–35 years old with a diagnosis of psychosis, who were currently under the care of a UK specialist National Health Service (NHS) Mental Health team (Early Intervention for Psychosis Team). Nutritional knowledge was assessed at baseline across the groups. Readiness to Change eating habits was measured at baseline and a further two time points post intervention. Although there were no significant between group differences, the PNI group elicited both the most progression in terms of readiness to change eating habits, but also the most regression. The use of MI may be anti-therapeutic for those who are not ready to consider make changes to their eating habits, and this requires further investigation. Greater emphasis on the importance of assessing and selecting who is most likely to benefit from interventions is necessary.